NILAI-NILAI PENDIDIKAN KARAKTER DALAM BUDAYA NENGAH NYAPPUR - Muhammad Candra Syahputra (Program Studi Pendidikan Agama Islam Fakultas Ilmu Tarbiyah Dan Keguruan, 2020)
Lampung indigenous people have valuable local wisdom that has the values of character education. The purpose of this research is to form a form of support to the government that continues to campaign for character education as an effort to restore the original character of the moral Indonesian nation and this study also aims to discover how the values of character education in the local wisdom of Lampung indigenous people namely Nengah Nyappur. This research uses descriptive-qualitative method to explore various data with library research. Nengah Nyappur as one of the elements of the philosophy of life of the people of Lampung has a character value in the form of tolerance, courtesy, and cooperation. These three character values are rooted in the daily lives of the indigenous people of Lampung. Referring to the presidential regulation of the Republic of Indonesia Number 87 of 2017 concerning Strengthening Character Education, Education Units and School/Madrasah Committees consider the adequacy of educators and education personnel, availability of facilities and infrastructure, local wisdom and opinions of community leaders and or religious leaders outside the School/Madrasah Committee. The third point about local wisdom feels the need for writers to review as one of the bases of character education, the writer offers local wisdom of Lampung. The findings of this study are that the values contained in Nengah Nyappur are still very relevant until now and can be applied in the family environment, community environment, and school environment.